정보시스템 구축과 내부 감사 제어에 대한 고찰 - 변진식(Byun jinsik) (韓國컴퓨터情報學會誌, 2003)
Along with trends of other countries, the Ministry of Information and Communication in Korea decided to operate an Information System Audit Institution for raising qualify of computer network facilitated in state organ and public institution, and to construct effective construction of information system. The aim of the audit institution is applying it to public information business, establishing an information system audit qualification system, and upbringing Private audit organs. The Ministry of Information and Communication realized that although the demand of information system area audit is explosively expanding, the National Computerization Agency cannot satisfies the demand and realize to have audit control for the information of national business as well. The Ministry of Information and Communication plan to enforce the audit on public information business by correlate with information business. The ministry enforce that the supervisory company has major roll to audit and national import business decided by the Information Promotion Committee is subject to have audit control. Therefore, in this paper, the contents of internal audit among internal/external audit will be presented. 우리나라에서도 정보통신부는 국가 및 공공기관의 전산망 품질수준을 제고하고 효율적인 정보시스템 구축을 지원하기 위해 공공부문 정보화사업에 대한 감리 제도의 활성화, 정보시스템 감리 자격제 도입, 민간 감리 기관의 육성 등을 주요 내용으로 하는 $\ulcorner$정보시스템 감리 제도 도입계획$\lrcorner$ 을 마련해 본격 시행에 들어가기로 했다. 정통부가 이번에 정보시스템 감리제도를 크게 강화하기로 한 것은 최근 들어 국가 및 공공기관을 중심으로 정보시스템 분야의 감리 수요가 폭발적으로 증가하고 있음에도 불구하고 한국전산원에 감리 업무가 집중되고 있어 공공부문의 감리 수요를 충족시키기 힘든 데다 국가정보화 사업에 대한 감리 제도의 도입 필요성이 점차 높아지고 있기 때문으로 풀이된다. 정통부는 감리제도를 활성화하기 위해 공공부문 정보시스템 감리를 정보화사업과 연계해 제도화한다는 방침을 세우고 공공부문 정보화사업에 대한 감리를 주관기관의 판단에 일임하되 정보화 추진위원회가 정한 국가적인 중요 사업에 대해선 감리를 의무화하기로 했다. 이에 대해 내. 외부 감사중 내부감사에 대해 그 내용을 파악해 보자는 데 그 목적이 있다.